REGIONAL ECONOMIC SECURITY: ANALYSIS BY REGIONS AND DEVELOPMENT OF A RISK INDEX - Abduraxmanova Gulnora Kalandarovna; Maxmudova Muxlisa Qodirjon qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article improves scientific and methodological approaches to assessing economic security and proposes a new integrated mechanism designed to overcome the limitations of existing composite methods. The proposed index is based on a system of indicators that covers macro-stability, labor market conditions, socio-economic balance, and interregional spatial effects. The findings confirm that the author-developed index is practically useful for an in-depth analysis of regional disparities, identifying spatial effects within economic security, and formulating targeted regional development policies.